Non-Formal Education through Paguyuban and Pesilat Communities as a Strategy for Conflict Reconciliation among Silat Schools - Afif Syaiful Mahmudin; Wathoni, Kharisul (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
The ongoing violence and conflict between pencak silat schools in Madiun seriously threatens the stability and harmony of the community. This research aims to explore the extent to which non-formal education can play a role as a strategy for conflict reconciliation between two pencak silat schools in Madiun, namely Persaudaraan Setia Hati Terate (PSHT) and Persaudaraan Setia Hati Winongo (PSHW). This research employed a qualitative approach with a phenomenological design. The data were collected through in-depth interviews, observations, and documentation to identify symbolic interactions related to spirituality and culture. The findings reveal that religious activities, informal dialogue, and the implementation of joint spiritual rituals can create symbolic meanings between the two schools, thereby strengthening fraternal bonds and reducing tensions. The emergence of these activities can foster a shared identity that breaks down sectarian barriers, while also internalizing peace education values such as social cohesion, forgiveness, and mutual respect among the schools. This research has contributed to the study of conflict reconciliation in Indonesia through a spiritually based, non-formal education approach, utilizing a conflict reconciliation model that integrates local traditions. These findings can serve as a reference for policymakers and community leaders in designing sustainable and dialogical approaches to mitigate social conflicts in other multicultural environments that occur in Indonesia.